2018
DOI: 10.3390/molecules23020239
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effect of Tremella Polysaccharides against Cyclophosphamide-Induced Immunosuppression in Mice

Abstract: Polysaccharides are closely associated with immune regulation, but there are different polysaccharide effects from different sources. In this study, the aim was to investigate the effect of tremella polysaccharides (TP) in cyclophosphamide-induced immunodeficient mice. We observed the thymus and spleen index, liver and spleen pathological changes, and the levels of IL-2, IL-12, INF-γ, TGF-β and Ig G in serum, and we also noted the mRNA expression of IL-1β, IL-4, IL-12 and TGF-β in liver and spleen. Besides, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 36 publications
4
39
0
Order By: Relevance
“…It not only activates macrophages but also activates NK cells [54]. And it is a highly potent antiviral cytokine with broad-spectrum immunomodulatory effects [55]. It is reported that the beginning of IL-2 function depends on B and T lymphocytes, which is one of the most important lymphoid factors regulating the immune function of the body [56].…”
Section: Effects Of Tp On Genes Expression Of Immune-related In the Smentioning
confidence: 99%
“…It not only activates macrophages but also activates NK cells [54]. And it is a highly potent antiviral cytokine with broad-spectrum immunomodulatory effects [55]. It is reported that the beginning of IL-2 function depends on B and T lymphocytes, which is one of the most important lymphoid factors regulating the immune function of the body [56].…”
Section: Effects Of Tp On Genes Expression Of Immune-related In the Smentioning
confidence: 99%
“…T. fuciformis is rich in active polysaccharides (Wu et al, 2019). On recent years, many reports had shown that T. fuciformis polysaccharides possessed various bioactivities (Wu et al, 2019), including antioxidation, anti-tumor (Chen, 2010), anti-aging (Wen et al, 2016), immunomodulatory (Zhou et al, 2018), and anti-inflammator (Lee et al, 2016;Yang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Administration of Cy can lead to a sudden change in Th1/Th2 bias, resulting in immunosuppression [ 19 ]. In previous studies, the immunological effects of Cy were found to decrease the absolute number of T cells, proliferation of lymphocytes, Th1 cell produced cytokines (IL-2, IL-12, and IFN- γ ), and Th2 produced cytokine (IL-4) [ 20 ].…”
Section: Introductionmentioning
confidence: 99%